Hodnocení finanční situace podniku a návrhy na její zlepšení - Sapoušek, Ondřej (Vysoké učení technické v Brně. Fakulta podnikatelská, 2015)
Bakalářská práce se zabývá hodnocením finanční situace firmy OK Group a.s. v letech 2010 až 2013. Na základě výsledků provedené finanční analýzou jsou navrhnuta řešení zjištěných problémů, která mají vést ke zlepšení finanční situace společnosti.

Bachelor thesis deals with assessment of the financial situation of the company OK Group a.s. in years from 2010 to 2013. The results of the financial analysis are used for proposed solutions and they should lead to improve financial situation of the company.
Evaluation of the Financial Situation of a Company and Proposals to its Improvement
Keywords: Finanční situace podniku; absolutní ukazatele; horizontální analýza; vertikální analýza; metody finanční analýzy.; Financial situation of the company; absolute indicators; horizontal analysis; vertical analysis; methods of financial analysis.